Reversible Tumorigenesis Induced by Deficiency of Vasodilator-Stimulated Phosphoprotein - Liu, Keyi (American Society for Microbiology, 1999)
Random homozygous knockout (RHKO) is an antisense RNA strategy capable of identifying genes whose homozygous functional inactivation yields a selectable phenotype in cells growing in culture. Using this approach, we isolated NIH 3T3 fibroblast clones that showed the ability to form colonies on 0.5% agar and tumors in nude mice. The gene inactivated in one of these clones was found to encode VASP (vasodilator-stimulated phosphoprotein), a previously identified protein that binds to components of the cadherin-catenin junctional complex and has been implicated in cell-cell interactions, the formation of actin filaments, and the transmission of signals at the cytoskeleton-membrane interface. Fibroblasts made deficient in VASP by RHKO showed loss of contact inhibition, and consequently, continued cell division past confluence. Restoration of VASP function by reversal of RHKO yielded cells that had lost the neoplastic capabilities acquired during RHKO. Overproduction of VASP mRNA in the sense or antisense orientation from expression constructs introduced by transfection into naive NIH 3T3 fibroblasts also resulted in neoplastic transformation, implying that normal cell growth may require the maintenance of VASP expression within a narrow range. Our results implicate VASP in tumorigenesis and/or cancer progression.